Ultrahigh-Q terahertz sensor based on simple all-dielectric metasurface with toroidal dipole resonance. (28th September 2021) - Jiang, Xiao-Qiang; Fan, Wen-Hui; Chen, Xu; Yan, Hui
Abstract: A simple all-dielectric metasurface with symmetric structure, exhibiting strong toroidal dipole (TD) resonance and ultrahigh quality factor ( Q -factor), is proposed. The physical mechanisms of the TD resonance are investigated by calculating the electromagnetic field and the scattering power of multipoles. Simulated results demonstrate that the Q -factor is up to 3.71 × 10 4 and the corresponding figure of merit is 636.7. Moreover, the TD resonance can be excited under both x - and y -polarized incident terahertz waves due to the symmetric structure. The remarkable performances make the proposed metasurface has feasible capability for biological and chemical sensing in terahertz range.